Students’ Perceptions and Attitudes toward English: A Descriptive Quantitative Study at SMPIT Ar Rahmah Pacitan - Apriyanti, Chusna; Putri, Nala Zainuna (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
ABSTRACT This study aims to describe students’ perceptions and attitudes toward English at SMPIT AR Rahmah Pacitan. The research employed a quantitative descriptive design and involved all students in Grades 7, 8, and 9 as the sample using a census sampling technique. Data were collected through a 20–item Likert scale questionnaire, which consisted of four dimensions: importance and usefulness, confidence, motivation, and environmental support. The data were analyzed using descriptive statistics, which involved calculating mean scores for each item, each dimension, and the total score. The findings show that students’ overall perception and attitude toward English fall into the high category. The highest dimension is importance and usefulness, indicating that students view English as valuable and relevant to their future needs. Meanwhile, confidence, motivation, and environmental support also fall within the high category, although slightly lower. These results suggest that students at SMPIT AR Rahmah Pacitan have positive perceptions and attitudes toward English learning, which provides a supportive foundation for the development of more effective instructional strategies.